Rice Ovate Family Protein 2 (OFP2) alters hormonal homeostasis and vasculature development. (December 2015) - Schmitz, Aaron J.; Begcy, Kevin; Sarath, Gautam; Walia, Harkamal
Highlights: We functionally characterize the first OVATE-like transcription factor, OsOFP2, in rice. A conserved putative NES motif is required for normal OsOFP2 localization. OsOFP2 alters rice morphology and hormone, lignin, and vasculature gene expression. OsOFP2 expression is vascular bundle-specific and influences vascular positioning. Abstract: OFP (Ovate Family Protein) is a transcription factor family found only in plants. In dicots, OFPs control fruit shape and secondary cell wall biosynthesis. OFPs are also thought to function through interactions with KNOX and BELL transcription factors. Here, we have functionally characterized OsOFP2, a member of the OFP subgroup associated with regulating fruit shape. OsOFP2 was found to localize to the nucleus and to the cytosol. A putative nuclear export signal was identified within the OVATE domain and was required for the localization of OsOFP2 to distinct cytosolic spots. Rice plants overexpressing OsOFP2 were reduced in height and exhibited altered leaf morphology, seed shape, and positioning of vascular bundles in stems. Transcriptome analysis indicated disruptions of genes associated with vasculature development, lignin biosynthesis, and hormone homeostasis. Reduced expression of the gibberellin biosynthesis gene GA 20-oxidase 7 coincided with lower gibberellin content in OsOFP2 overexpression lines. Also, we found that OsOFP2 was expressed in plant vasculature and determined that putative vascular development KNOX and BELL proteins interact with OsOFP2. KNOX and BELL genes are known to suppress gibberellin biosynthesis through GA20ox gene regulation and can restrict lignin biosynthesis. We propose that OsOFP2 could modulate KNOX-BELL function to control diverse aspects of development including vasculature development.